2018
DOI: 10.1088/1757-899x/288/1/012097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prunus Dulcis Extract against Total Cholesterol Level in Mice that Given Monosodium Glutamate

Abstract: Abstract. Monosodium glutamate (MSG) is chemical compound that when it is used excessively it can cause various side effects such as hypercholesterolemia. Hypercholesterolemia will result in coronary heart disease (CHD), which is a disease causing death. The aim of study was assessing the effect of almond nut/ Prunus dulcis extract against total cholesterol level in mice that given MSG. This study was randomized post test controlled group design. The sample consisted of 30 mice (Mus musculus L. Strain DDW) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Neonatal administration of MSG produces hypothalamus induced obesity (Braga et al, 2001). Another study showed that 4 g MSG treated group has an increase in the body weight, but mild doses did not show any increase in the body weight (Sari et al, 2018).…”
Section: Bioscience Biotechnology Research Communicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Neonatal administration of MSG produces hypothalamus induced obesity (Braga et al, 2001). Another study showed that 4 g MSG treated group has an increase in the body weight, but mild doses did not show any increase in the body weight (Sari et al, 2018).…”
Section: Bioscience Biotechnology Research Communicationsmentioning
confidence: 96%
“…Neonatal administration leads to immature blood brain barrier (Boonnate et al, 2015), degenerative changes in hypothalamic arcuate nucleus (Holzwarth-Mcbride et al, 1976), reduced serotonin and cognitive functioning (Moneim et al, 2018), pyknotic Purkinje and granule cells with infl amed cells in the cerebellum (Hashem et al, 2012). Another study showed that 4 g MSG treated group had an increase in the body weight, but mild doses did not show any increase in the body weight (Sari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment by utilizing natural resources such as herb plants has become a tradition of people around the world. Traditional medicine comes from the herb plant that has safe side effect compared to the chemical medicine [13,14]. There have been many studies conducted in conjunction with the treatment of DM, one of them with the utilization of herb plants.…”
Section: Sari and Anggrainimentioning
confidence: 99%